2020
DOI: 10.48550/arxiv.2005.09838
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Parallelizable Method for Missing Internet Traffic Tensor Data

Abstract: Recovery of internet network traffic data from incomplete observed data is an important issue in internet network engineering and management. In this paper, by fully combining the temporal stability and periodicity features in internet traffic data, a new separable optimization model for internet data recovery is proposed, which is based upon the t-product and the rapid discrete Fourier transform of tensors. Moreover, by using generalized inverse matrices, an easy-to-operate and effective algorithm is proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…T-product and T-SVD Kilmer and her collaborators proposed T-product and T-SVD factorization of third order tensors [6,7,8,14,21,22,23]. Works on applications of T-product and T-SVD factorization include [3,9,11,15,18,19,20,24]. It is shown that they are very useful in applications.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…T-product and T-SVD Kilmer and her collaborators proposed T-product and T-SVD factorization of third order tensors [6,7,8,14,21,22,23]. Works on applications of T-product and T-SVD factorization include [3,9,11,15,18,19,20,24]. It is shown that they are very useful in applications.…”
Section: Related Workmentioning
confidence: 99%
“…The T-product operation, T-SVD decomposition and tensor tubal ranks were introduced by Kilmer and her collaborators in [6,7,8,23]. It is now widely used in engineering [3,9,14,15,18,19,20,21,22,24].…”
Section: Tensor-tensor Product Operationsmentioning
confidence: 99%
“…The T-product operation, T-SVD factorization and tensor tubal ranks were introduced by Kilmer and her collaborators in [3,4,5,18]. They are now widely used in engineering [1,7,11,12,13,14,15,16,17,19,20]. In particular, Kilmer and Martin [4] proposed T-SVD factorization.…”
Section: Introductionmentioning
confidence: 99%
“…The matrix SVD factorization (1.1) was extended to third order tensors as T-SVD factorization by Kilmer and Martin [4,5]. The T-SVD factorization has been found wide applications in engineering and tensor computation [1,3,6,7,8,10,11,13,14,15,16,17,18,19,21,20,22,23]. In T-SVD factorization, an m × n × p third order real tensor A is decomposed to the tensor product of an m × m × p orthogonal tensor U, an m × n × p real f-diagonal tensor S, and an n × n × p orthogonal tensor V:…”
Section: Introductionmentioning
confidence: 99%